2021
DOI: 10.5812/ijpbs.114432
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms and General Mental Health Problems During the COVID-19 Pandemic in Iran: A Web-Based Cross-sectional Survey

Abstract: Background: The COVID-19 pandemic as a stressor can harm the community's mental health. Iran is one of the first countries to be severely affected by COVID-19 since February 2020. Objectives: This study aimed to assess the rates of COVID-19-related Posttraumatic Stress Symptoms (PTSS) and the general mental health burden among the Iranian population during the pandemic and to explore the potential influencing factors. Methods: Through a web-based cross-sectional survey, based on social media, data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In our study, female respondents had higher PCL-5 scores compared to males. This is consistent with previous studies, which showed that the prevalence of mental health burden and PTSD was higher in females than males during the COVID-19 pandemic (9,15,16). The reason can be the greater prevalence of common risk factors in females, consisting of anxiety disorders and preexisting depressive, chronic environmental stress, fluctuations in ovarian hormone levels and hypersensitivity to emotional stimuli, and domestic violence, which may be exacerbated during a pandemic (9,10).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, female respondents had higher PCL-5 scores compared to males. This is consistent with previous studies, which showed that the prevalence of mental health burden and PTSD was higher in females than males during the COVID-19 pandemic (9,15,16). The reason can be the greater prevalence of common risk factors in females, consisting of anxiety disorders and preexisting depressive, chronic environmental stress, fluctuations in ovarian hormone levels and hypersensitivity to emotional stimuli, and domestic violence, which may be exacerbated during a pandemic (9,10).…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have confirmed demographic characteristics to be significant variables influencing the predisposition to PTSD (9,10). Similarly, our study highlighted the greater possibility of higher PCL-5 scores in younger adults, consistent with several previous studies conducted during the COVID-19 pandemic (9,17,18).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies have shown that insecurity, due to the death and fear caused by the COVID-19 pandemic, further exacerbates anxiety symptoms in older adults [ 7 , 8 ]. In addition, studies from several countries have noted that the COVID-19 pandemic significantly increased anxiety levels in older adults [ 9 , 10 , 11 , 12 , 13 ]. In particular, during the lockdown of the COVID-19 pandemic, people were required to practice home isolation, which exacerbated anxiety symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%